Local analogs of high-redshift galaxies: Interstellar medium conditions. Issue Volume 11:Issue S321(2015) (21st March 2017) - Bian, Fuyan; Kewley, Lisa J.; Dopita, Michael A.; Juneau, Stephanie
Abstract: Local analog galaxies play an important role in understanding the properties of high-redshift galaxies. We present a method to select a type of local analog that closely resembles the ionized interstellar medium conditions in high-redshift galaxies. These galaxies are selected based on their locations in the [OIII ]/Hβ versus [NII ]/Hα nebular emission-line diagnostic diagram. The ionization parameters and electron densities in these analogs are comparable to those in z ≃ 2 − 3 galaxies, but higher than those in normal SDSS galaxies by ≃ 0.6 dex and ≃ 0.9 dex, respectively. We find that the high sSFR and SFR surface density can enhance the electron densities and the ionization parameters, but still cannot fully explain the difference in ISM condition between nearby galaxies and the local analogs/high-redshift galaxies.